VIth World Congress on Science and Football, Book of Abstracts, January 16-20, 2007, Antalya, Turkey - Poster Presentations - Strength and Speed (Journal of Sports Science & Medicine, 2007)
Summaries on the following topics: P-098 Effects of strength training and practice on soccer throw-in performance P-099 Power output during repeated maximal sprints is better maintained after maximal strength training compared to hypertrophy training in soccer players P-100 Developing effect by eccentric - concentric contraction in two directions on speed components of soccer and basketball players P-101 Change of explosive muscle strength in sub-20 soccer players in a season P-102 Change in physical performance of sub-20 soccer players submitted in maximal strength training program P-103 Biomechanical symmetry differences in the goalkeeping diving save P-104 Aerodynamic factors in soccer: A comprehensive review